Pengaruh Kompensasi Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada Pt. Indonesia Thai Summit Plastech (Karawang Barat) - Algi Nadiansyah; Dewi Kurniawati (JURNAL MANAJEMEN PENDIDIKAN, 2026)
THE EFFECT OF COMPENSATION AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT PT. INDONESIA THAI SUMMIT PLASTECH (WEST KARAWANG) This study aims to examine the effect of compensation and work environment on employee performance at PT. Indonesia Thai Summit Plastech (West Karawang). Employee performance is a critical factor in achieving organizational objectives; therefore, effective human resource management through appropriate compensation and a conducive work environment is essential. This study employed a quantitative approach with a causal research design. The population consisted of 294 employees, while the sample comprised 75 respondents selected using the Slovin formula with a simple random sampling technique. Data were collected through a structured questionnaire using a Likert scale and analyzed using multiple linear regression with SPSS version 27. The results indicate that compensation has a positive and significant effect on employee performance, with a t-value of 2.349 and a significance value of 0.022 (<0.05). The work environment also has a positive and significant effect on employee performance, with a t-value of 3.148 and a significance value of 0.002 (<0.05). Simultaneously, compensation and the work environment have a significant effect on employee performance, as indicated by an F-value of 31.836 and a significance value of <0.001. The Adjusted R Square value of 0.455 indicates that compensation and the work environment explain 45.5% of the variance in employee performance, while the remaining 54.5% is influenced by other factors not examined in this study. These findings suggest that improving a fair compensation system and creating a supportive work environment can enhance employee performance at PT. Indonesia Thai Summit Plastech (West Karawang).